THE MODERN TECHNOLOGIES FOR THE CONTROL OF KNOWLEDGE AND SKILLS OF EDUCATION RECIPIENTS - Kondur, Oksana; Ratushniak, Valerii (Mountain School of Ukrainian Carpaty, 2020)
The article analyzes the modern interpretation of the concept of "knowledge control". The main functions of control of knowledge and skills of the educational recipients are educational, diagnostic, stimulating, educational functions, function of assessment. The management function is of paramount importance. In addition to controlling the level of learning, it is important to make decisions about optimizing the educational process. Types of control knowledge and skills are classified according to place in the process of achieving the didactic goal of educational activities.To increase the effectiveness of training, it is necessary to practice different ways of organizing control. Because proper and rational organization of control of knowledge and skills contributes to identifying gaps in the knowledge and skills of the learners, determining their level of readiness to learn new material. Control also forms students' self-control skills. Testing is an effective way to control knowledge.The current state of technology development tests are set using test shells of the stationary type or on online platforms. Cloud services are spreading. They allow you to reach remote audiences and evaluate real-time knowledge and skills. We recommend using cloud technologies for professional and regional specialties (for example, for students of nonstationary form of study from remote mountain regions).